Microtexturing of the Conductive PEDOT:PSS Polymer for Superhydrophobic Organic Electrochemical Transistors. (22nd January 2014) - Gentile, Francesco; Coppedè, Nicola; Tarabella, Giuseppe; Villani, Marco; Calestani, Davide; Candeloro, Patrizio; Iannotta, Salvatore; Di Fabrizio, Enzo
Abstract : Superhydrophobic surfaces are bioinspired, nanotechnology artifacts, which feature a reduced friction coefficient, whereby they can be used for a number of very practical applications including, on the medical side, the manipulation of biological solutions. In this work, we integrated superhydrophobic patterns with the conducting polymer PEDOT:PSS, one of the most used polymers in organic electronics because highly sensitive to ionized species in solution. In doing so, we combined geometry and materials science to obtain an advanced device where, on account of the superhydrophobicity of the system, the solutions of interest can be manipulated and, on account of the conductive PEDOT:PSS polymer, the charged molecules dispersed inside can be quantitatively measured. This original substrate preparation allowed to perform electrochemical measurements on ionized species in solution with decreasing concentration down to 10 −7 molar. Moreover, it was demonstrated the ability of the device of realizing specific, combined time and space resolved analysis of the sample. Collectively, these results demonstrate how a tight, interweaving integration of different disciplines can provide realistic tools for the detection of pathologies. The scheme here introduced offers breakthrough capabilities that are expected to radically improve both the pace and the productivity of biomedical research, creating an access revolution.